THE EFFECT OF DISCLOSURE OF CARBON EMISSIONS AND ECO EFFICENCY ON COMPANY VALUE - Maharani Juniar Mulyadi Salim; Murtanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
There are many threats to climate change accompanied by environmental damage. This is able to create a paradigm for assessing environmental performance in companies that are directly related to the environment. Regarding the impact of a business's business activities on the environment, it is a challenge for companies to find ways to reduce their environmental impact and make disclosures as a form of responsibility every year. The sample in this research uses energy sector companies for the period 2020 to 2023. The method used in this research is a panel data regression model with the results of research on carbon emissions disclosure and eco-efficiency having no effect on company value.